Comparing Some Productivity Traits for Sorghum Genotypes Under Nitrogen Fertilizer Levels (Damascus University Journal of agriculture sciences, 2023)
A field experiment was conducted in Izraa research station, during growing seasons 2017/2018 & 2018/2019 to comparing some productivity traits of six sorghum genotypes (Acsad 6, Acsad 44, Acsad 47, Acsad 49, IS10586 & IS19457) under four Nitrogen levels (o, 80, 100 & 120 kg N.ha-1). The experiment laid out according to split-split plot arrangement using randomized complete block design RCBD with three replications. No significant differences were found between nitrogen levels for number ofgrains on head and weight of 100 kernel. Whereas, significant increasing was found when using 120 kg N.ha-1 for plant high by ratio 13.2% & 8.0%, and for grain yield  by ratio 44.8% & 23.5% comparing with 0 & 80 kg N.ha-1 respectively. The genotype IS19457 exceed significantly over other genotypes in most traits. So it is recommended to use it in breeding program
Keywords: Sorghum; Genotypes; Nitrogen Fertilizer; Grain Yield